Customer Nontransactional Value Cocreation in an Online Hotel Brand Community: Driving Motivation, Engagement Behavior, and Value Beneficiary. (May 2022) - Shin, Hakseung; Perdue, Richard R.
To better understand engagement behaviors in online hospitality brand communities, the purpose of this research was to understand hotel customers' online engagement behaviors, associated cocreated nontransactional values, and the underlying drivers. Netnography analysis and qualitative surveys along with multiorder categorization analysis were used. The netnography results indicate that hotel customer engagement behaviors cocreate five types of value. Importantly, these values accrue in different levels to not only the customer, but also to other customers and to the firm. Analyses of a subsequent qualitative survey data validated the four factors driving these engagement behaviors and, importantly, found that the motivational drivers vary by type of engagement. A conceptual framework of value cocreation via customer engagement is proposed.